1983
DOI: 10.1055/s-2007-969907
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Liquid Chromatographic Separation of Isoflavones and Structural Elucidation of Isoflavone 7-O-glucoside 6″-malonates from Cicer arietinum

Abstract: An efficient separation by HPLC of isoflavone aglycones and glucosides on reversed - phase columns is described. The main isoflavone constituents of CICER ARIETINUM L., various TRIFOLIUM species, BAPTISIA AUSTRALIS L. and ONONIS SPINOSA L. are formononetin 7-O-glucoside 6''-malonate and biochanin A 7-O-glucoside 6''-malonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…The present study does not allow us to define the mechanisms by which high concentrations of cells or their products inhibit hyphal growth. In addition to producing stimulatory compounds, suspension-cultured cells can also accumulate a number of antifungal compounds, either as normal cell metabolites or in response to biotic and environmental elicitation (Hahlbrock & Grisebach, 1979;Takeya & Itokawwa, 1982;Kabayashi & Ohat, 1983;Koster, Strack & Barz, 1983;Ingham, Tahara & Dziedzic, 1988;Lamb et al, 1989). VA mycorrhizal fungi are considered to be non-pathogenic in nature, but they are capable of causing a host response before penetration (Gemma & Koske, 1988), typical host defense responses in the first stages of the interaction (Spanu et al, 1989), and host accumulation of antifungal phenolic compounds (Morandi, Bailey & Gianinazzi-Pearson, 1984) capable of reducing hyphal growth (Siqueira, 1983;Wacker, Safir & Stephens, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The present study does not allow us to define the mechanisms by which high concentrations of cells or their products inhibit hyphal growth. In addition to producing stimulatory compounds, suspension-cultured cells can also accumulate a number of antifungal compounds, either as normal cell metabolites or in response to biotic and environmental elicitation (Hahlbrock & Grisebach, 1979;Takeya & Itokawwa, 1982;Kabayashi & Ohat, 1983;Koster, Strack & Barz, 1983;Ingham, Tahara & Dziedzic, 1988;Lamb et al, 1989). VA mycorrhizal fungi are considered to be non-pathogenic in nature, but they are capable of causing a host response before penetration (Gemma & Koske, 1988), typical host defense responses in the first stages of the interaction (Spanu et al, 1989), and host accumulation of antifungal phenolic compounds (Morandi, Bailey & Gianinazzi-Pearson, 1984) capable of reducing hyphal growth (Siqueira, 1983;Wacker, Safir & Stephens, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The ethylacetate fractions were brought to dryness and the residue was dissolved in 2 00 (il methanol. These extracts were used for analysis and quantifi cation of the phenolic compounds by HPLC-techniques as described earlier [12,32].…”
Section: Isolation O F Phenolic Constituents Fro M Protoplasts and Vamentioning
confidence: 99%
“…Several classes of secondary constituents, D-conflgurated amino acids, endproducts of pesticide degradation and interme diates of phytohormon production were described as malonyl conjugates [10,11]. In addition to chickpea and other previously analyzed plants [12] very recent investigations also demonstrated that the isoflavones in soybean and alfalfa mainly accu mulate as 7-0-glucoside-6"-0-malonates [13,14]. Furthermore, the pterocarpan phytoalexins of chickpea cell suspension cultures have been found to accumulate as malonyl conjugates [15].…”
Section: Introductionmentioning
confidence: 99%
“…Initial surveys testing for the presence of nod-gene inducer conjugates in roots used more rigorous precautions to preserve fragile molecules (17). Differences from the above protocol included extraction of48-h-old roots with cold (<00C) acetone and drying under N2 at 15°C or less.…”
Section: Isolation and Purification Of Flavonoidsmentioning
confidence: 99%